Successful revascularisation of near total amputation of the upper limb after ten hours of warm ischaemia - Merican, A.M.; Kwan, M.K.; Cheok, C.Y.; Wong, E.L.; Ahmad, T.S. (Malaysian Medical Association, 2005)
Severe crush injuries to the upper limb may require a formal amputation with devastating consequences to the patient. We report a patient with a near total amputation at the level of mid-forearm who underwent revascularization and salvage of his hand. The operative details of this case are described. It is the first time that such a patient has been treated successfully by plastic surgeons and orthopedic surgeons at the Sultan Qaboos Hospital, Salalah. Awareness of the possibility of salvage should be spread among health care personnel as well as the need for immediate attention by a multispeciality team. Literature related to the operative technique, contraindications and long term results is reviewed.